2015
DOI: 10.1371/journal.pone.0130287
|View full text |Cite
|
Sign up to set email alerts
|

MURC/cavin-4 Is Co-Expressed with Caveolin-3 in Rhabdomyosarcoma Tumors and Its Silencing Prevents Myogenic Differentiation in the Human Embryonal RD Cell Line

Abstract: The purpose of this study was to investigate whether MURC/cavin-4, a plasma membrane and Z-line associated protein exhibiting an overlapping distribution with Caveolin-3 (Cav-3) in heart and muscle tissues, may be expressed and play a role in rhabdomyosarcoma (RMS), an aggressive myogenic tumor affecting childhood. We found MURC/cavin-4 to be expressed, often concurrently with Cav-3, in mouse and human RMS, as demonstrated through in silico analysis of gene datasets and immunohistochemical analysis of tumor sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Cavin-4 is only abundant in muscle cells and is able to interact with cavin-2. Faggi et al has reported cavin-4 is important in the differentiation process of rhabdomyosarcoma in combination with caveolin-3 (38).…”
Section: Introductionmentioning
confidence: 99%
“…Cavin-4 is only abundant in muscle cells and is able to interact with cavin-2. Faggi et al has reported cavin-4 is important in the differentiation process of rhabdomyosarcoma in combination with caveolin-3 (38).…”
Section: Introductionmentioning
confidence: 99%